Safety and Efficacy of Tirofiban in Rescue Treatment for Acute Intracranial Intraprocedural Stent Thrombosis - Sun, Lili; Zhang, Jinping; Song, Yun; Zhao, Wei; Zheng, Meimei; Zhang, Jun; Yin, Hao; Wang, Wei; Meng, Yao; Tang, Jiyou; Han, Ju (Frontiers in Neurology, 2020)
Background and Purpose: The incidence of acute intraprocedural stent thrombosis (AIST) during stenting of intracranial atherosclerotic stenosis (ICAS) has seldom been reported and evidence regarding the treatment of AIST is lacking. We aim to investigate the incidence of AIST during stenting of ICAS in our institute, assess the preliminary efficacy and safety of rescue treatment of tirofiban for these patients. Methods: From September 2016 to May 2019, all symptomatic ICAS patients who underwent intracranial stenting in our institute were prospectively registered into this study, of which patients with AIST were retrospectively reviewed to extract baseline characteristics, perioperative management, procedural details, angiographic, and clinical outcomes. Rescue treatment of tirofiban for AIST was assessed by recanalization of the culprit vessel and periprocedural death, hemorrhage, and ischemic stroke. Results: Acute intraprocedural stent thrombosis developed in 12 (6.2%) patients within 30 min after stent placement of 194 patients. All 12 cases were successfully recanalized with modified Treatment in Cerebral Ischemia (mTICI) 3 and Arterial Occlusive Lesion (AOL) 3 after rescue treatment of tirofiban alone. There was no perioperative death or any hemorrhagic complication. Three patients suffered perioperative ischemic stroke. Conclusions: We observed a non-negligible rate of AIST during intracranial stenting procedures for ICAS. Intra-arterial bolus followed by intravenous tirofiban infusion seems to be efficacious and safe for AIST during stent placement for ICAS, without increasing the rate of hemorrhagic complications and death.